2013
DOI: 10.1016/j.mce.2013.03.008
|View full text |Cite
|
Sign up to set email alerts
|

A protective role for FGF-23 in local defence against disrupted arterial wall integrity?

Abstract: Increasing interest is focusing on the role of the FGF-23/Klotho axis in mediating vascular calcification. However, the underpinning mechanisms have yet to be fully elucidated. Murine VSMCs were cultured in calcifying medium for a 21d period. FGF-23 mRNA expression was significantly up-regulated by 7d (1.63 fold; P<0.001), with a concomitant increase in protein expression. mRNA and protein expression of both FGFR1 and Klotho were confirmed. Increased FGF-23 and Klotho protein expression was also observed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 53 publications
4
64
0
1
Order By: Relevance
“…medium (Invitrogen) for 20 mins. After 24 h, cells were cultured in control or high inorganic phosphate (P i ) medium (α-minimal essential medium supplemented with 10% fetal calf serum, 1% gentamycin and 2 mM Na 2 HPO 4 /NaH 2 PO 4 pH7.4), which we have previously shown to induce calcification after 7 days in culture 11. At day 3 in high P i medium, the medium was changed and a repeat transfection mix was added to the fresh medium.…”
Section: Methodsmentioning
confidence: 99%
“…medium (Invitrogen) for 20 mins. After 24 h, cells were cultured in control or high inorganic phosphate (P i ) medium (α-minimal essential medium supplemented with 10% fetal calf serum, 1% gentamycin and 2 mM Na 2 HPO 4 /NaH 2 PO 4 pH7.4), which we have previously shown to induce calcification after 7 days in culture 11. At day 3 in high P i medium, the medium was changed and a repeat transfection mix was added to the fresh medium.…”
Section: Methodsmentioning
confidence: 99%
“…Due to its role in mineralization, FGF23 was clinically associated with vascular calcification (13,14,31,48,52,62). However, most recently it has been shown that FGF23 does not promote (42,54), but may actually prevent, vascular calcification (76). Nevertheless, FGF23 may have other effects on the vasculature.…”
mentioning
confidence: 99%
“…Irrespective of phosphorous levels, FGF-23 independently predicts survival chances of chronic HD patients [28,29]. However, whether FGF-23 plays an active pathogenetic role in uremic vascular calcification remains uncertain, and experimental studies have exhibited opposing effects on the calcification process [30,31]. Recently, there is growing evidence of the role of the Wnt-ß-catenin signaling pathway in vascular calcification.…”
Section: Discussionmentioning
confidence: 99%